2010
DOI: 10.1021/ja107769z
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide-Substituted Nitronyl Nitroxide and Iminonitroxide

Abstract: We report on the highly compact nitroxide-substituted nitronyl nitroxide 1 and iminonitroxide 2; they have isoelectronic structures with trimethylenemethane. These diradicals are stable under aerated conditions at room temperature and have large positive exchange interactions: J/k(B) = +390 K (H = -2JS(1)(/)(2)·S(1/2)) for 1 and J/k(B) ≈ +550 K for 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…As shown in Figure 6b,t he calculated spin densities of (DAA-PTZ) + + -NN spread across the whole molecule and tightly combine, thereby providing al arge spin-polarization effect. [8][9][10] We then carried out theoretical calculations (Gaussian 09 [19] and ORCA program package [20] ). Structuralo ptimization was achieveda tt he UB3LYP/6-31G* level of theory by using the polarizablec ontinuumm odel (PCM) methodw ithb utyronitrile as the solvent, and the magnetic tensors were calculated at the UBLYP/Sapporo-DZP level by using the COSMO method with acetonitrile as the solvent: g xx-calcd = 2.0075, g yy-calcd = 2.0027, g zz-calcd = 2.0055, g ave-calcd = 2.0052, j D calcd /hc j = 0.0056 cm À1 ,a nd j E calcd /hc j = 0.0003 cm À1 (see Tables S2-S5 in the Supporting Information).…”
Section: Gabrmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 6b,t he calculated spin densities of (DAA-PTZ) + + -NN spread across the whole molecule and tightly combine, thereby providing al arge spin-polarization effect. [8][9][10] We then carried out theoretical calculations (Gaussian 09 [19] and ORCA program package [20] ). Structuralo ptimization was achieveda tt he UB3LYP/6-31G* level of theory by using the polarizablec ontinuumm odel (PCM) methodw ithb utyronitrile as the solvent, and the magnetic tensors were calculated at the UBLYP/Sapporo-DZP level by using the COSMO method with acetonitrile as the solvent: g xx-calcd = 2.0075, g yy-calcd = 2.0027, g zz-calcd = 2.0055, g ave-calcd = 2.0052, j D calcd /hc j = 0.0056 cm À1 ,a nd j E calcd /hc j = 0.0003 cm À1 (see Tables S2-S5 in the Supporting Information).…”
Section: Gabrmentioning
confidence: 99%
“…The experimentally determinedi ntramolecular ferromagnetic interaction of J 1 /k B =+320 Ki sr easonable when compared with the results of our previous studies on radical-substituted radicalc ations [8,9] and other diradical studies. [10] The origin of the strong intramolecular ferromagnetic interactions is considered to derive from the delocalization of the spin densities. The two molecularo rbitals of the unpaired electrons in the triplet state (singlyo ccupied molecular orbitals,S OMOs) are distributed on either the (DAA-PTZ) + + or NN site (see Figure S8), which results in the tight combination of the spin densities on the (DAA-PTZ) + + and NN sites (Figure6b).T his is a commonf eature of tripletdiradicals at room temperature.…”
Section: à àmentioning
confidence: 99%
See 1 more Smart Citation
“…1012 Several factors such as nature of the linkers between two spins, conformations, substituents and environment (e.g., temperature, solvent, etc) control the exchange coupling magnitude in biradicals. 27 Through conformational constraint into the co-planarity of two radical moieties with m-phenylene 10,28,29 or simple direct linkage, 30 stable trimethylenemethane (TMM)-type biradicals with large positive exchange interactions have been recently obtained which show great potential as building blocks for robust magnetic materials. In contrast, biradicals with rigid geometries holding two nitroxide moieties approximately orthogonal to one another have weak exchange coupling but show enhanced DNP properties.…”
Section: Introductionmentioning
confidence: 99%
“…They have also shown a sharp emission band of [Eu(hfac) 3 IN] centred at 615 nm upon excitation with 212 nm light [22] (see some books [23,24] for details). Recently, Hasegawa also found that some organic diradicals composed of two radical groups bridged with a methylene group such as iminonitroxide-substituted iminonitroxide, referred to as IN-IN hereafter, first synthesised by Suzuki et al [25,26], being coexistent with Eu or Tb ion show highly efficient lanthanide-ion-specific photoemission [27]. Suzuki et al also synthesised Cu complexes with the similar kind of diradical ligands [28].…”
Section: Introductionmentioning
confidence: 99%